Postpartum health of working mothers : A prospective study - Majorie Ensayan, Janting; Cheah, Whye Lian; Helmy, Hazmi (Academy of Family Physicians of Malaysia, 2023)
Introduction: Most working women experience poor physical and mental health during their postpartum period. is prospective study aimed to describe the physical and mental health issues faced by working mothers during their postpartum period. Methods: Respondents were recruited using the proportional sampling method among mothers who attended the Maternal and Child Health Clinic in the Kuching division in Sarawak, Malaysia. Faceto-face interview was conducted using a questionnaire that consisted of items on socio-demographic data as well as perinatal, prenatal and postpartum factors, and the Edinburgh Postnatal Depression Scale and a checklist of 28 specic postpartum symptoms were used during the rst 6 weeks and after 12 weeks of childbirth. Results: A total of 281 respondents participated in this study. Fatigue (42.7%), back or neck pain (36.3%), breast discomfort (16.4%), dizziness (13.5%) and nipple irritation (11.0%) were among the most common symptoms experienced by the mothers during the rst 6 weeks after childbirth. ere was a signicant decrease in the physical symptom scores of the respondents from the rst 6 weeks to after 12 weeks of childbirth (1.73±1.96 vs 0.16±0.42; P<0.0005). A signicant decrease was also found in the depression scores (6.26±4.26 vs 1.35±1.85, P<0.0005). Conclusion: e prevalence of postnatal depression was higher during the rst 6 weeks of postpartum than after 12 weeks of postpartum. Screening and treatment of poor postpartum mental health among working women are essential owing to the impacts on occupational outcomes.